2017
DOI: 10.1111/crj.12641
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension associated with combined fibrosing mediastinitis and bronchial anthracofibrosis: A retrospective analysis in a single Chinese hospital

Abstract: Introduction: Both fibrosing mediastinitis (FM) and bronchial anthracofibrosis (BAF) are unique diseases. The combined appearance of FM and BAF is extremely rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…FM can be divided into the localized type (localized soft tissue mass, often accompanied by calcification) and diffuse type (diffuse infiltrative mass, no capsule, unclear boundary, generally no cystic change or necrosis) according to the typical manifestations of CT, and the pathological types are granulomatous type and non-granulomatous type ( 8 ). Granulomatous FM is mostly related to tuberculosis, fungi, histoplasmosis infection, or sarcoidosis, while non-granulomatous FM is mostly caused by non-infectious factors, such as autoimmune diseases, drugs, dust, radiation, etc., or it is difficult to identify the cause of the idiopathic disease ( 9 ). This case considered localized FM according to the signs of the contrast-enhanced chest CT. As mentioned above, the causes of FM vary from region to region in the world.…”
Section: Discussionmentioning
confidence: 99%
“…FM can be divided into the localized type (localized soft tissue mass, often accompanied by calcification) and diffuse type (diffuse infiltrative mass, no capsule, unclear boundary, generally no cystic change or necrosis) according to the typical manifestations of CT, and the pathological types are granulomatous type and non-granulomatous type ( 8 ). Granulomatous FM is mostly related to tuberculosis, fungi, histoplasmosis infection, or sarcoidosis, while non-granulomatous FM is mostly caused by non-infectious factors, such as autoimmune diseases, drugs, dust, radiation, etc., or it is difficult to identify the cause of the idiopathic disease ( 9 ). This case considered localized FM according to the signs of the contrast-enhanced chest CT. As mentioned above, the causes of FM vary from region to region in the world.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Xu et al have reported eight patients with PH; attributed to the combination of bronchial anthracofibrosis and fibrosing mediastinitis 9. Interestingly, patients had a combination of bronchial stenoses and elevated PA pressures, evidence of hypoxaemia and PA stenoses.…”
mentioning
confidence: 99%